Fluid management of cardiopulmonary bypass during pulmonary endarterectomy for CTEPH patients impacts perioperative outcome - K. Furrer, MD; D. Bettex, MD; T. Horisberger; I. Inci, MD; N.G. Nagaraj; H.-T. Morselli; B. Battilana; R. Schuepbach, MD; S. Ulrich, MD; M. Hebeisen, MSc; I. Opitz, MD (JHLT Open)
Background: Pulmonary endarterectomy (PEA) using deep hypothermic circulatory arrest (DHCA) and cardiopulmonary bypass (CPB) is the preferred treatment for chronic thromboembolic pulmonary hypertension (CTEPH). Crystalloid priming solutions cause hemodilution with disadvantages, and no standard exists for PEA. This study evaluates CTEPH patient outcomes after adding 5% human albumin (HA) to the CPB-prime and hemodilution solution during PEA. Methods: The effect of the CPB-protocol change was evaluated by comparing patients operated under the old and new protocols in a 1:1 propensity score match based on age, sex, and preoperative peripheral vascular resistance (PVR). Results: Matching resulted in 56 patients (28 per group) between July 1, 2010, and May 31, 2020. The new protocol group had a lower intraoperative fluid balance (1.85 vs 6.76 liters, p < 0.001), vasoactive-inotropic score (VIS) (8.7 vs 17.7, p = 0.04), shorter operative- (407 vs 451 min, p = 0.03), and hospitalization time (LOS) (18 vs 27 days, p = 0.008). Morbidity and mortality at 30- and 90-days were similar in both groups. The new protocol was associated with reduced intraoperative fluid balance after adjustment for operative time (−3.7 liters [95% CI −5.2, −2.1], p < 0.0001). Lower intraoperative fluid balance was associated with shorter hospitalization in the intensive care unit, intubation time, LOS, and lower VIS (p = 0.0011, 0.0013, 0.008, <0.0001, respectively). The protocol change shortened LOS, independent of operative time, by 27% [95% CI, 44%, 6%], p = 0.02. Conclusions: Priming and maintenance protocol for CPB with the addition of 5% HA had a beneficial effect on intraoperative fluid balance and improved outcome after PEA for patients with CTEPH.